2021
DOI: 10.1021/acs.jcim.1c00515
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Relative Binding Affinity for Reversible Covalent Inhibitors by Free Energy Perturbation Calculations

Abstract: Covalent inhibitors are assuming central importance in drug discovery projects, especially in this pandemic scenario. Many research groups have focused their attention on inhibiting viral proteases or human proteases such as cathepsin L (hCatL). The inhibition of these critical enzymes may impair viral replication. However, molecular modeling of covalent ligands is challenging since covalent and noncovalent ligand-bound states must be considered in the binding process. In this work, we evaluated the suitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…31 In a recent example Bonatto et al showed, for human cathepsin L, how FEP can be used to estimate free energy changes. 32 Using a small set of nitrile-based reversible covalent cathepsin L inhibitors, the authors found that FEP to predict relative BFEs, using the covalent state, generated more predictive results than using the noncovalent state. The respective MUE and Pearson correlation coefficients were reported as 1.33 (0.92) and 0.69 (0.89) for the noncovalent (covalent) transformations.…”
Section: ■ Covalent Inhibitorsmentioning
confidence: 99%
“…31 In a recent example Bonatto et al showed, for human cathepsin L, how FEP can be used to estimate free energy changes. 32 Using a small set of nitrile-based reversible covalent cathepsin L inhibitors, the authors found that FEP to predict relative BFEs, using the covalent state, generated more predictive results than using the noncovalent state. The respective MUE and Pearson correlation coefficients were reported as 1.33 (0.92) and 0.69 (0.89) for the noncovalent (covalent) transformations.…”
Section: ■ Covalent Inhibitorsmentioning
confidence: 99%
“…Irreversible warheads can serve as a starting point for developing temporary binders; by providing appropriate chemical modifications, irreversible warheads' reactivity can be altered to make them reversible [ 47 ]. Bonatto et al predicted the binding-free energies of reversible covalent inhibitors using free energy perturbation procedures and evaluated their binding affinity [ 48 ]. Fanfrlk and colleagues demonstrated the principle of rational design of reversible covalent vinylsulfone inhibitors using an enhanced quantum mechanics-based scoring function (QM) [ 49 ], whereas Schirmeister and co-workers used a hybrid approach combining quantum mechanics and molecular mechanics (QM/MM) for the design of covalent vinyl sulfone-based inhibitors [ 50 ].…”
Section: Targeted Covalent Inhibitors and “Warhead” Reactivitymentioning
confidence: 99%
“…Several computational studies have used a simple molecular model for exploring the reactivity of covalent irreversible inhibitors. Other simulations were performed using more complex systems, which include the effect of the enzymatic environment on the chemical reaction. For instance, Warshel and Mondal have used the empirical valence-bond approach for assessing the chemical step and the PDLD/S-LRA/β method for evaluating the non-covalent part of the binding process of an α-ketoamide inhibitor of SARS-CoV-2 main protease, and others have proposed that the covalently bound complex is sufficient for predicting the binding free energy and selectivity of covalent inhibitors. , Zhang and co-workers have used free energy perturbation (FEP) and molecular dynamics (MD) simulations for calculating the total binding free energy of reversible covalent inhibitors of calpain . For pairs of ligands sharing the same warhead, they concluded that FEP is predictive of binding free energies .…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition mechanisms of cysteine proteases , and protein kinases have been studied. We have investigated inhibition mechanisms of cysteine proteases using FEP and the quantum mechanics/molecular mechanics (QM/MM) approach. , In the QM/MM approach, a small part of the system is modeled quantum-mechanically with an MM force field describing the protein and solvent . The QM/MM approach can be used to calculate the reactivity of a covalent inhibitor while characterizing the mechanism of inhibition at the atomic level.…”
Section: Introductionmentioning
confidence: 99%